Kemampuan Pemecahan Masalah Matematis Siswa: Quasi Experimental melalui Model Pembelajaran Problem Based Instruction (PBI) di SD Negeri Kabupaten Indragiri Hilir - Defi Defi (Lembaga Anotero Scientific Pekanbaru, 2023)
This research started with the problem of the low mathematical problem-solving ability of fourth grade students at SDN 004 Sungai Salak. This can be seen in the results of tests of mathematical problemsolving abilities obtained by students, the results of observations and interviews with teachers. This study aims to determine the effect of the application of the Problem Based Instruction model on the mathematical problemsolving abilities of fourth grade students at SDN 004 Sungai Salak and to determine the students' mathematical problemsolving abilities after being taught with the Problem Based Instruction model. The type of research used is quasi-experimental research with The Time Series Experiment. The population in this study were all fourthgrade students at SDN 004 Sungai Salak, which totaled 21 people and consisted of 1 class. The sampling technique is a saturated sample because the population is less than 30 people. The data collection technique in this study used a mathematical problemsolving ability test. Data analysis technique used in this study, namely the t-test. Based on the research findings, it can be concluded that the mathematical problemsolving ability of students who take part in learning using the Problem Based Instruction model is higher than students who take part in conventional learning.